International views on disability measures moving toward comparative measurement - Altman, Barbara Mandell; Barnartt, Sharon N. (Research in social science and disability ;, 2006)
Disability policy has become an increasingly important issue in countries around the world. More and more, as populations are exposed to war and civil conflicts, natural disasters, environmental poisons along with the effects of normal aging, accidents and poverty, disability has become a growing public health and civil rights problem. In order to develop reasonable policy solutions, countries need accurate, reliable estimates of the size and make up of their disabled population. Comparisons of policy solutions cross-nationally require that the data that is used as the basis for the policy decisions is comparable. At the same time that the world has determined an important need for data on populations with disability, the data that is available is still haphazard and not comparable. The UN has begun to address this need with a publication, the "Guidelines and Principles for the Development of Disability Statistics in 2001", and through the authorization of the formation of the Washington Group, an informal, temporary organization in the mode of a City Group. As a voluntary organization of National Statistical Office representatives, the purpose of the Washington Group is to address selected problems in statistical methods associated with the measurement of disability internationally. The papers in this volume reflect a sampling of the work done to this point by the Washington Group to address this important public health problem. The collection describes the background of disability measurement as the work of the group started from an international perspective and identifies other work being done in this area. It also provides snapshots of the data that is currently available and in use along with how the data is used in a variety of countries. Finally, a section on methodological issues identifies some insight as well as suggested solutions to key problems that will need to be addressed if the Group is to accomplish its task. This volume includes papers that examine the statistical problems associated with the measurement of disability internationally. It looks at country specific issues as well as overarching methodologies. It is an important contribution to disability and public policy.